An Extragastrointestinal Tumor Diagnosed as a Vaginal Mass during Pregnancy. (25th October 2022) - Ando, Reo; Taniguchi, Shuichi; Arita, Shuji; Aman, Murasaki; Marutsuka, Kousuke; Shimamoto, Tomihiro
Abstract : We report a case of an extragastrointestinal stromal tumor diagnosed as a vaginal mass during pregnancy. The mass was detected during routine examination at 24 weeks of gestation. At 26 weeks, the patient underwent transvaginal ultrasonography and magnetic resonance imaging, which revealed a blood flow-rich mass of approximately 50 × 30   mm in the rectovaginal septum. At 29 weeks of gestation, we resected the mass vaginally and the pathological diagnosis was a gastrointestinal stromal tumor. Chemotherapy was withheld until after full-term birth because the proliferation index of the tumor cells was low. The patient delivered a healthy infant. Imatinib was commenced at 1 month postpartum, with no recurrence or metastasis after 2.5 years. An extragastrointestinal stromal tumor as a vaginal mass in pregnancy has not been reported; however, our case suggests that the tumor should be considered a differential diagnosis of a vaginal mass in pregnancy.